UPLC-ESI-QTRAP-MS-Based Metabolomics Revealed Changes in Biostimulant-Related Metabolite Profiles in Zingiber mioga Flower Buds During Development - Jiao Xie; Yahan Zhou; Zhifei Cheng; Huijuan Liu (Metabolites)
Background: The composition and abundance of biostimulants are important factors in the formation of the flavour and nutritional value of flower buds, as well as key factors influencing their growth and development. Methods: Therefore, the variation characteristics of phenolic acids, nucleotides and derivatives, alkaloids, lipids, tannins, terpenoids and others in Z. mioga flower buds during the growth and development were studied by UPLC-MS/MS. Results: The vast majority of the 204 compounds identified in this study showed a clear upward trend throughout the bud development, accumulating to a maximum at maturity. Considering both the PCA and HCA results, the four growth stages were effectively separated, indicating the significant differences between the stages, and the late developmental stage (SG3) was likely to be the key node in growing and developing flower buds. Differential metabolites that affected the stage division were screened by OPLS-DA. Conclusions: Correlation analysis based on the key top 50 differential metabolites showed that biostimulant-related compounds collectively influenced the growth and maturation of Z. mioga flower buds in a joint and comprehensive manner.